Gestión financiera y su impacto en la ejecución presupuestaria del gad municipal de buena fe periodo 2022- 2023. - Panchana Arias , Cinthya Stefany (2025)
This research examines the impact of financial management on the execution of the institutional budget of the Municipal (GAD) of Buena Fe during the 2022–2023 period. The main objective is to determine how administrative and financial decisions influence the fulfillment of budgetary goals, within the context of a public administration focused on optimizing efficiency, effectiveness, and transparency in the use of public resources. The study adopts a quantitative approach with a descriptive and correlational scope and is based on the analytical-deductive method. Various techniques were used for data collection, including document review, analysis of budget sheets and the Annual Operating Plan (POA), as well as surveys conducted with staff from the GAD’s financial department. The data obtained were processed statistically, allowing for the analysis of the relationship between financial management and budget execution. The results indicate that proper financial planning, along with efficient revenue collection and resource allocation, contributes positively to meeting budgetary objectives. However, shortcomings were identified in monitoring and control processes, which hinder the achievement of institutional goals. In conclusion, the study emphasizes the need to strengthen planning and control mechanisms, provide training for technical staff in public management, and promote an organizational culture based on transparency and accountability. This research provides valuable insights for improving financial management in local governments.